Tétano em pequenos ruminantes: estudo retrospectivo dos principais achados clínico-epidemiológicos em 11 casos - Almeida, A. C. S. [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Paes, Antonio Carlos [UNESP]; Megid, Jane [UNESP]; Oliveira, V. B. [UNESP]; Franco, M. M. J. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2012)
A retrospective study of major clinical and epidemiological findings was performed in 11 cases of tetanus observed in eight sheep and three goats from 1998 to 2008. The cases occurred predominantly in animals aging from five days to two years, in winter season, with history of recent wounds or surgical procedures. Muscle rigidity and muscular tremors (72.0%), tachycardia/dyspnea (54.5%), change of placement of ears (45.4%), protusion of the third eyelid (27.2%), hypersensitivity to external stimulus (18.1%), and elevation of ears (18.1%) were the most common clinical signs.
Tetanus in small ruminants: retrospective study of major clinical and epidemiological findings in 11 cases
Keywords: tétano; Clostridium tetani; ovinos; caprinos; tetanus; sheep; goat; epidemiology; clinical signs; Clostridium tetani